Unwarranted influence Dwight D. Eisenhower and the military-industrial complex - Ledbetter, James (Icons of America., 2011)
In Dwight D. Eisenhowerʹs last speech as president, on January 17, 1961, he warned America about the "military-industrial complex," a mutual dependency between the nationʹs industrial base and its military structure that had developed during World War II. After the conflict ended, the nation did not abandon its wartime economy but rather the opposite. Military spending has steadily increased, giving rise to one of the key ideas that continues to shape our countryʹs political landscape. In this book, published to coincide with the fiftieth anniversary of Eisenhowerʹs farewell address, journalist James Ledbetter shows how the government, military contractors, and the nationʹs overall economy have become inseparable. Some of the effects are beneficial, such as cell phones, GPS systems, the Internet, and the Hubble Space Telescope, all of which emerged from technologies first developed for the military.